The The Anatomical Image Information Difference MRI Vertebrae cervical Sagittal In Sequence Short Tau Inversion Recovery (STIR) With Pre Saturation Variation - Masrochah, Siti; Octaviani, Ema; Ningrum, Farah Hendara; Handoko, Bagus Dwi (Proceeding ICMA-SURE; Vol 1 No 1 (2021): Proceeding ICMA-SUREDO - 10.20884/2.procicma.2021.1.1.4420, 2021)
Pre saturation is one of the methods used to reduce artifacts. pre saturation can be applied to any sequence where the number and location can be adjusted as needed. The aim of this research is to know the difference of MRI anatomical image of vertebrae cervical sagittal on sequence of short tau inversion recovery (STIR) with pre saturation variation. This study used MRI Phillips 3 T. Data were collected from 2 patients and 8 volunteers with 3 variations of pre saturation (anterior, anterior – superior, and anterior - inferior) with 30 images obtained. The MRI image was qualitatively assessed by two radiology specialists by filling out the questionnaire provided in the form of Spinal Cord anatomy, Cerebrospinal Fluid, Corpus Vertebrae, Invertebral Discus and Processus Spinosus. The Result on Friedman's different test results, for the highest mean rank is pre-saturation variation in anterior - inferior with mean rank value 2.39. For the second pre-saturation variations in anterior - superior with mean value of 1.90. And in the last order that is on pre saturation in anterior with mean value equal to 1.71. on Wilcoxon different test showed the level of significance on variations of pre saturation Anterior and Anterior - Superior with value 0.340. In the variation of pre saturation Anterior and Anterior - Inferior showed a significant difference in two variations with p value <0,001. For variations of pre saturation Anterior - superior and Anterior - Inferior significance level valued 0.003.